Resiliência e determinação: caminhos formativos de uma pedagoga em construção - Santos, Mariliana Viana dos (Brasil, 2024)
This academic memorial is a training memorial and seeks to describe and analyze my educational trajectory throughout the Pedagogy course. Knowing that my undergraduate training trajectory is connected with my life trajectory, in this memorial I narrate episodes from my childhood, schooling, the Pedagogy course and my professional work. This is how I recount memories of my childhood; the desire to study; Some school experiences that stood out the most in the trajectory of my life, pleasure, pride, discoveries, joys, sadness, disappointments. I narrate the classes of my first grade teacher, who was my source of inspiration for pursuing a teaching career, and I explain why I chose the Pedagogy course. About my experiences in Pedagogy, I discuss aspects of training as a teacher through the connection between theory, lived experiences and pedagogical practice. I emphasize this event as the culmination of the realization of the dream of achieving the desired academic training. It also reflects the process of knowledge construction during the training and learning period, as well as the transformations and redimensioning in my pedagogical practices, given a new understanding of the pedagogue's theories and educational concepts.